CAPITAL STRUCTURE PERBANKAN SYARIAH DI ASIA TENGGARA: SEBUAH PENDEKATAN EMPIRIS - Astiwi Indriani; Endang Tri Widyarti; Shoimatul Fitria (Al Tijarah, 2017)
This research is performed in order to analyze capital structure of Islamicbanking by examining the effect of Return on Asset, Assets Structure,Current Ratio, and size to Debt Ratio in Southeast Asia during period 2012-2015. Sampling technique used is purposive sampling with criteria as follows(1) The Financial Statements are presented by Islamic Banking duringobservation period 2012-2015; (2) Having complete data which suitable forthe research; (3) Debt Ratio is positif; (4) Profitability is positif. The databased on financial report of each bank 2012-2015 and sample was acquired18 Islamic Banking. The statistic analysis that used in this research wasmultiple linear regression. The research result showed that the ROA havenegative and insignificance, Assets Structure and current ratio have negativesignificance, size have positif significance. Adjusted R square value as 0,601show that 60,1 percent variation of debt ratio can be explained by the variationof the four independent variables, while the remaining 39,9 percent isexplained by other factors.